Mortality Rates do not Differ among Patients Prescribed Various Vitamin d Agents. Issue 1 (January 2015) - Bond, T. Christopher; Wilson, Steve; Moran, John; Krishnan, Mahesh
Background: Limited well-controlled research exists examining the impact of different formulations of oral vitamin D on clinical outcomes in dialysis patients, specifically those on peritoneal dialysis. For this retrospective mortality analysis, we compared mortality rates of patients on 3 of the most commonly prescribed vitamin D agents. Methods: We examined 2 years (7/1/2008 to 6/30/2010) of oral medication records of peritoneal dialysis patients from a large US dialysis organization. Patients were identified whose physicians prescribed a single form of vitamin D (calcitriol, paricalcitol, or doxercalciferol) for ≥ 90% of all patient-months. We excluded incident patients (< 90 days on dialysis) and patients whose physicians treated < 5 peritoneal dialysis patients at a dialysis facility, and we assessed mortality. Results: The analysis inclusion criteria identified 1, 707 patients. The subset in this analysis included 12.6% of all prevalent peritoneal dialysis patients and 11.8% of prevalent patient-months. Patients with physicians who predominately prescribed calcitriol had a lower mortality rate: 9.33 (confidence interval (CI) 7.06, 11.60) deaths per 100 patient-years than the doxercalciferol, 12.20 (CI 9.34, 15.06) or paricalcitol, 12.27 (CI 9.27, 15.28) groups. However, these differences were not statistically significant. A Cox proportional hazards model, adjusting for differences in age, vintage, gender, race, body mass index, and comorbidities also showed no significant differences. Conclusions: For this peritoneal dialysis population, instrumental variable analyses showed no significant difference in mortality in patients taking the most common oral vitamin D formulations (calcitriol, doxercalciferol, paricalcitol).